Dyslipidemias in normotensive and hypertensive individuals - NM Igboh; D Onwubiko; LN Chigbu; CI Emuchey; NK Nnamah; CA Onyesom; EN Agomuo; CA Maduagwuna; KME Iheanacho (Journal of Applied Sciences and Environmental Management)
:The present work was carried out to compare the effects of age and antihypertensive therapy on lipid profile in hypertensive and normotensive individuals. A total of 150 individuals were used for the study.100 hypertensive under therapy were used and 50 normotensive served as control. Serum lipid (Cholesterol (T -chol) , triglyceride (TG), Phospholipids (PL),High density lipoprotein( HDL-chol ), Low density lipoprotein( LDLchol) and very low density lipoprotein (VLD L- chol) were biochemical parameters monitored. The normotensive studied had mean age of 50 + 11 years and blood pressure of 117 + 6 / 77+ 6 mmHg. The hypertensive had mean age of 55 + 10 years and blood pressure of 177+25 /103 + 10 mmHg.The study revealed that there was a highly significant effect of age on total cholesterol in hypertensive than normotensive individuals .The mean total cholesterol (T -chol) and triglyceride (TG) were (156+11, and 59 + 4) mg/dl respectively for the normotensives; and hypertensive the means were 166 + 13 for the T –chol and 66+ 7 mg/dl for triglyceride (P<0.05). Similarly, a significant lower phospholipids level of 158+8 mg /dl was obtained for normotensives, hypertensives had a mean (165+ 11 mg/dl, P<0.05). However, HDL-chol was lower in hypertensives (57+ 10) mg/dl than in normotensives (64+ 13) mg/dl). Hypertensive patients also recorded higher mean values of LDL-chol (95+ 17) mg/dl than the normotensives with mean values of 81+ 15 mg/dl for LDL- chol. Marginally higher level of VLD L- chol was observed in hypertensive patients as well compared to normotensive individuals VLD L- chol(13+ 2)mg/dl and 12 + 1 mg/dl for VLD Lchol( P<0.05).